WEBVTT
00:00:00.434 --> 00:00:08.084
Using the information in the figure, calculate the coefficient of kinetic friction, rounding the result to the nearest two decimal places.
00:00:08.464 --> 00:00:16.724
Given that the mass of the body is 28 kilograms and that the acceleration due to gravity, 𝑔, equals 9.8 meters per second squared.
00:00:17.304 --> 00:00:25.994
Taking a look at our figure, we see our body which is on some surface, moving along with an acceleration to the right of 2.2 meters per second squared.
00:00:26.394 --> 00:00:34.734
This acceleration is due to a force of 155 newtons that’s being applied at an angle of 45 degrees to the horizontal.
00:00:35.334 --> 00:00:46.114
Knowing this, along with the fact that the mass of our body — we’ll call it 𝑚 — is 28 kilograms, we want to solve for the coefficient of kinetic friction between the body and the surface.
00:00:46.664 --> 00:00:52.854
We can begin solving for this coefficient by first sketching in all the forces that are acting on our body.
00:00:53.004 --> 00:00:54.874
This is called a free-body diagram.
00:00:55.274 --> 00:00:58.604
For one thing, we know that our body is subject to the force of gravity.
00:00:59.134 --> 00:01:07.734
We also know that there’s an applied force, we’ll call it 𝐹 sub 𝐴, which is given as 155 newtons, acting at a 45-degree angle on the body.
00:01:08.104 --> 00:01:12.954
Furthermore, there’s a normal or reaction force acting straight up from the surface.
00:01:13.224 --> 00:01:16.944
And lastly, there’s a frictional force; we’ll call it 𝐹 sub 𝑓.
00:01:17.174 --> 00:01:19.684
And this opposes the motion of our object.
00:01:20.044 --> 00:01:23.934
That’s always true of friction, which is how we knew that it acted to the left.
00:01:24.534 --> 00:01:29.584
Now that we know all the forces acting on our object, we can recall Newton’s second law of motion.
00:01:29.914 --> 00:01:35.894
This tells us that the net force that acts on somebody is equal to that body’s mass times its acceleration.
00:01:36.344 --> 00:01:45.914
Now because motion in the vertical direction is independent of motion in the horizontal direction, we can apply Newton’s second law to either one independently.
00:01:46.244 --> 00:01:54.764
In other words, we could say that the net force in the horizontal plane acting on our body is equal to the object’s mass multiplied by its horizontal acceleration.
00:01:55.104 --> 00:02:03.004
And indeed, this is the dimension we’ll focus on because we want to solve for the coefficient of kinetic friction, which is bound up in the force of friction.
00:02:03.474 --> 00:02:13.424
When we say that, we just mean that the force of friction acting on an object that’s in motion is equal to the coefficient of kinetic friction multiplied by the normal force acting on the object.
00:02:13.884 --> 00:02:15.074
So, here’s what we’ll do.
00:02:15.364 --> 00:02:23.204
Focusing first on this horizontal direction, let’s clear a bit of space on screen and apply Newton’s second law in this horizontal plane.
00:02:23.654 --> 00:02:27.984
The first thing we’ll do is establish sign conventions, positive and negative.
00:02:28.404 --> 00:02:34.484
Note that the acceleration given to us in our problem statement is a positive value and that acceleration is to the right.
00:02:34.724 --> 00:02:41.284
We’ll say then that any force or motion in that direction is positive, and any force or motion in the other direction is negative.
00:02:41.664 --> 00:02:50.424
As we study the forces acting horizontally in our free-body diagram, we see that there’s a component of the applied force that acts horizontally.
00:02:50.734 --> 00:02:54.094
And then there’s the friction force which acts entirely in this direction.
00:02:54.454 --> 00:03:08.924
Given a 45-degree right triangle where the hypotenuse is our applied force magnitude, 155 newtons, we can solve for this horizontal leg of that triangle by multiplying 𝐹 sub 𝐴 by the cos of 45 degrees.
00:03:09.224 --> 00:03:13.274
That then accounts for the positive horizontal force acting on our body.
00:03:13.594 --> 00:03:16.464
We then subtract from that the frictional force.
00:03:16.754 --> 00:03:22.684
That force recall is equal to the coefficient of kinetic friction, what we want to solve for, times the normal force.
00:03:23.034 --> 00:03:26.984
This accounts for all of the horizontal forces acting on our mass.
00:03:27.214 --> 00:03:33.014
And therefore, by Newton’s second law, this sum is equal to mass times acceleration in the horizontal direction.
00:03:33.444 --> 00:03:41.704
We’re given 𝐹 sub 𝐴 as well as the mass and acceleration of our body, but we don’t know 𝐹 sub 𝑁 to let us solve for 𝜇 sub 𝑘.
00:03:42.224 --> 00:03:48.554
To solve for it, we’re actually going to need to apply Newton’s second law again, but this time in the vertical dimension.
00:03:49.074 --> 00:03:56.864
As we do this, we can set up the conventions that motion up is in the positive direction and motion down is in what we’ll call the negative direction.
00:03:57.344 --> 00:04:00.694
So, let’s consider the vertically acting forces on our body.
00:04:01.074 --> 00:04:03.534
First, there’s the normal force, 𝐹 sub 𝑁.
00:04:03.954 --> 00:04:08.264
Added to that is the vertical component of our applied force, 𝐹 sub 𝐴.
00:04:08.664 --> 00:04:14.834
Returning to our triangle, that side length is equal to 𝐹 sub 𝐴 times the sin of 45 degrees.
00:04:15.184 --> 00:04:20.134
And then lastly in the vertical direction, we have the weight force, 𝑚 times 𝑔, acting downward.
00:04:20.514 --> 00:04:22.674
By our convention, this force is negative.
00:04:22.914 --> 00:04:30.464
And by Newton’s second law, all of this is equal to the mass of our body times its acceleration in the vertical direction, what we’ll call 𝑎 sub 𝑣.
00:04:31.084 --> 00:04:35.794
We then realize that our object isn’t accelerating vertically, so this value is zero.
00:04:36.194 --> 00:04:38.724
That means these forces add up to zero.
00:04:39.084 --> 00:04:51.684
So, if we subtract this term from both sides of the equation and add this term to both sides, then we find an expression for the normal force, which is in terms of the weight force minus the vertical component of the applied force.
00:04:52.094 --> 00:04:56.424
We can then substitute this whole right-hand side in for 𝐹 sub 𝑁 here.
00:04:56.894 --> 00:05:02.544
And now, we have an expression we can use to solve for 𝜇 sub 𝑘, the coefficient of kinetic friction.
00:05:02.954 --> 00:05:11.504
This is because we know the numerical values of 𝐹 sub 𝐴, 𝑚, 𝑔, and 𝑎, as well as the sin and cos of 45 degrees.
00:05:11.844 --> 00:05:17.154
Before we plug in those values though, let’s rearrange this expression so that 𝜇 sub 𝑘 is the subject.
00:05:17.574 --> 00:05:22.254
First, we’ll subtract 𝐹 sub 𝐴, cos of 45 degrees, from both sides.
00:05:22.594 --> 00:05:26.694
Then, we’ll divide both sides of the equation by this expression in parentheses.
00:05:26.974 --> 00:05:30.184
And lastly, we’ll multiply both sides by negative one.
00:05:30.844 --> 00:05:32.404
We end up with this expression.
00:05:32.534 --> 00:05:34.954
And now, we’re ready to substitute in our values.
00:05:35.224 --> 00:05:37.694
𝐹 sub 𝐴 is 155 newtons.
00:05:38.014 --> 00:05:43.844
Both the cos and sin of 45 degrees is the square root of two over two.
00:05:43.844 --> 00:05:45.604
Our mass, 𝑚, is 28 kilograms.
00:05:45.884 --> 00:05:49.194
The acceleration, 𝑎, is 2.2 meters per second squared.
00:05:49.514 --> 00:05:54.344
And lastly, the acceleration due to gravity, 𝑔, is 9.8 meters per second squared.
00:05:54.974 --> 00:06:01.434
When we enter this expression on our calculator, to two decimal places, we find the result of 0.29.
00:06:01.784 --> 00:06:05.924
This is the coefficient of kinetic friction between our body and the surface.